Prevalence of Chlamydia trachomatis, Ureaplasma urealyticum, and Neisseria gonorrhoeae in Asymptomatic Women from Urban-Peripheral and Rural Populations of Cuenca, Ecuador - Sebastián Abad; Elizavet Neira; Lourdes Viñansaca; Samuel Escandón; Vivian Alejandra Neira (MDPI AG, 2022)
Background: Sexually transmitted diseases (STDs) are a serious public health issue due to their high prevalence and a substantial percentage of women being asymptomatic. The present study aimed to determine the prevalence of three STD-causative pathogens in asymptomatic women from Southern Ecuador, with the ultimate purpose of updating the epidemiological data and obtaining a timely diagnosis, which can prevent further complications. Methods: This cross-sectional study included 102 asymptomatic women from Cuenca, Ecuador, who underwent a cervical cytology examination. They met all the inclusion criteria and signed the consent form. Nucleic acids were extracted from each sample, and PCR and flow-through hybridization were performed to detect the pathogens responsible for three STDs. Descriptive and inferential statistics were used to define and describe the study population, obtain the frequency data, and measure central tendencies to determine possible associations among the variables. Results: We found that 49.02% of the participants were infected with at least one of the three microorganisms, with 48.04% and 2.94% carrying Ureaplasma urealyticum (UU) and Chlamydia trachomatis (CT), respectively. Neisseria gonorrhoeae (NG) infection was not observed. Among the participants, 1.96% presented co-infections with CT and UU. Approximately half of the participants presented with asymptomatic infections caused by at least one microorganism. Conclusions: This study demonstrates the importance of conducting regular STD screening programs for high-risk asymptomatic women.